An angel by her side : a heaven on earth novel - Reid, Ruth, 1963- (Reid, Ruth, 1963- Heaven on earth, 2017)
When Katie Bender<U+2019>s fiancé died in a tragic accident, so did her hope of finding love. Though heartbroken, Katie is also practical. In the years since the accident she has discovered her gift for teaching. But when a tornado destroys her small Amish settlement, including the schoolhouse, Katie doesn<U+2019>t know how she will provide for herself. Seth Stutzman arrived in Hope Falls days before the storm. And when he helps usher Katie and the children to safety, sparks fly. But Seth is only in town to help his brother, Amos, get back on his feet following the death of his wife. He can<U+2019>t afford to have feelings for Katie. Rebuilding the community is a huge task, and soon, Katie and Seth are working side by side. As they privately wrestle with their feelings for each other, another silent<U+2014>and ultimate<U+2014>battle for their hearts rages unseen. Sworn to protect what God has ordained, the mighty angel Elias appears to them as a mysterious visitor. And with his guidance, Katie and Seth find the courage to take the first small steps toward the life, and love, they were destined for.